Public participation in urban design with augmented reality technology based on indicator evaluation - Wang, Yuchen; Lin, Yin-Shan (Frontiers in Virtual Reality, 2023)
Decision-making processes in traditional urban design approaches are mainly top-down. Such processes have defects including not only taking a long time to examine design results but also leading to irreversible impacts after design implementation. Policymakers and researchers stress the importance of collaborating with different stakeholders in the process of urban design policy and guideline making in order to minimize these negative impacts. However, introducing public participation into urban design from the bottom up is challenging, especially when the process involves abstract urban design concepts such as indicators. This paper explores a new workflow aimed at enhancing public participation to cooperate in urban design work with the help of a newly designed platform tool powered by mobile augmented-reality technologies. The platform is intuitive to use and displays scenes of potential urban design results by superimposing the virtual models onto real-world environments on mobile devices. The public stakeholders are provided with this platform on-site to evaluate the initial values of urban design indicators by interacting with the prototype design along with an immersive experience. They can also grow familiar with the concepts of the given indicators during this process, which helps them better understand the implications of guidelines in future published urban design drafts and estimate the potential results. Their feedback is collected, which can help urban designers further optimize the indicators in urban design guideline making in order to improve their rationality. This process of urban design involving public participation is repeatable, which makes it possible to continuously adjust the design results. A user study was conducted to examine the platform’s usability and its ability to enhance public familiarity with the concepts of given indicators and their willingness to participate in urban design evaluation. The study also attests to the possibility of a workflow that integrates public feedback with the urban design process.